(untitled) (Latakia University Journal -Basic Sciences Series, 2023)
The organophosphorous compound tetraphenyl ester μ-imido-dithiodiphosphate was prepared Which has the P-N-P backbone and was used as a chelating ligand to prepare a complex with the element bismuth, as its use in the field of complex formation is one of the most important fields of research. The formation of the aforementioned compound was verified through spectroscopic studies using different technologies (IR spectroscopy - NMR spectroscopy - 1H-NMR and 31P-NMR). The work was continued using the prepared compound in a complexing process with the element bismuth in an alcoholic medium (methanol) by adding the alcoholic solution of the prepared compound to the alcoholic solution of aqueous bismuth nitratein a ratio of (1:3) at the laboratory temperature and at batches with continuous stirring. The formation of the complex was verified using IR- spectroscopy and melting point measurement. Bismuth and its compounds are generally considered safe and non-toxic, as complex compounds of bismuth are synthesized with a variety of different compounds with atoms bonding between them for biological evaluation.